Professional competence of customs officers (Ta'limning zamonaviy transformatsiyasi, 2024)
Professional issues do not lose their importance for future customs officers in the territory of the republic, and this motivates the search and development of effective methods and technologies aimed at developing professional competence in the process of training specialists.